The Embodiment of the Black Feminist Spirit In Iola Leroy, the Female Mulatto Protagonist, in Frances Harpers `Iola Leroy` - Asmarani, Ratna (English Language and Literature International Conference (ELLiC) Proceedings, 2017)
The aim of this paper is to analyze how the female protagonist in Harpers novel entitled Iola Leroy, although a mulatto, embodies the spirit of black feminism. To carry out the analysis, feminist literary criticism is used as the frame of analysis linked with gynocriticism. Several concepts concerning black feminism including empowerment, solidarity and sisterhood are used to support the frame of analysis. The result shows that the female mulatto protagonist, who does not know that she has black blood, all of a sudden experiences real slavery. This harsh turning point on her previously comfortable life leads to her new insight about slavery, about her race, and about her personal existence as a woman. The last point results not only in the emergence of the spirit of black feminism but also in the application of this spirit to other blacks, especially the black women. The convergence of thought and action makes the female mulatto protagonist turns out from the victim of slavery into the agent of change for the black race.